2016
DOI: 10.1002/micr.30047
|View full text |Cite
|
Sign up to set email alerts
|

Free versus perforator‐pedicled propeller flaps in lower extremity reconstruction: What is the safest coverage? A meta‐analysis

Abstract: In the lower limb the complications are not rare and many teams consider the free flaps to be safer. In this meta-analysis we provide evidence that failure and overall complications rate of perforator propeller flaps are comparable with free flaps. Although, partial necrosis is significantly higher for pedicled-propeller flaps than free flaps, in reality the success of coverage appears similar. © 2016 Wiley Periodicals, Inc. Microsurgery, 38:109-119, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
132
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(134 citation statements)
references
References 85 publications
(112 reference statements)
1
132
1
Order By: Relevance
“…A recent systematic review has shown that the overall failure rate and complication rate were similar to that of free tissue transfer, whereas partial necrosis of PPFs was more prevalent at 7% compared with 2.7% in free flaps. 14 It is important to realize the limitations of these flaps in the setting of lower limb trauma, they do not strictly represent the surgical panacea. In our practice, we make a balanced assessment based on the extent of trauma against bringing in free tissue on a patient-bypatient basis.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review has shown that the overall failure rate and complication rate were similar to that of free tissue transfer, whereas partial necrosis of PPFs was more prevalent at 7% compared with 2.7% in free flaps. 14 It is important to realize the limitations of these flaps in the setting of lower limb trauma, they do not strictly represent the surgical panacea. In our practice, we make a balanced assessment based on the extent of trauma against bringing in free tissue on a patient-bypatient basis.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to flap selection for reconstruction of the foot and ankle, Bekara et al agree that the success of free flaps and pedicled flaps in reality appears similar [28]. Gir et al believe that pedicled perforator flap use is a safe and reliable procedure for reconstructing soft tissue defects [29].…”
Section: Discussionmentioning
confidence: 99%
“…[16] In propeller flaps, because of pedicle bending, torsion partial/ total flap failure or venous problems can be observed. [17] Bekara et al [18] compared pedicled perforator flaps with free flaps in the reconstruction of the lower extremity and observed similar complications with both flaps. For the reconstruction of dorsal leg defects, the most appropriate flap was suggested to have a low donor site morbidity and for which the surgeon is more experienced.…”
Section: (A) (B) (C) (D)mentioning
confidence: 98%